THE CHALLENGES OF ATTRIBUTION OF INTERNATIONALLY WRONGFUL ACTS IN THE CYBERSPACE: A CRITICAL ANALYSIS OF CONTROL TESTS AND THE STANDARD OF PROOF IN INTERNATIONAL COURTS - Costa, Filipe Gomes Dias; Benn, Verônica Lúcia Hassler (Revista do CEPEJ, 2017)
This paper discusses the legal aspects, the challenges and difficulties that the traditional theories face when dealing with attribution on the cyber world. First, it will explain how the cyberspace is seen on the international law context. Following, it will be made a close examination of the standard of proof and the attribution tests, and how they work on regular situations. Then, it will be made a critical approach on the inefficiency of this rules when applied on State conducts on the cyberspace. Finally, the due diligence principle and the mitigation of the standard of proof will be analyzed as proper solutions to this dilemma, along with the need for proper codification and adaptation of the control tests to the particularities of the cyberspace.